Determination of phthalic acid esters and di(2-ethylhexyl) adipate in coffee obtained from capsules. (15th September 2022) - Domínguez-Hernández, Cristopher; Ortega-Zamora, Cecilia; González-Sálamo, Javier; Hernández-Borges, Javier
Graphical abstract: Highlights: First application of the QuEChERS method for the determination of plasticizers in coffee. Ten widely used plasticizers were determined in 27 samples of coffee made from capsules. The ammonium formate QuEChERS version provided less co-extracts than the original version. In general, the method showed high extraction capacity and moderate matrix effect. Some plasticizers were found in samples below the tolerable daily intake established for some of them. Abstract: In this work, the ammonium formate version of the QuEChERS method has been applied for the first time to the extraction of a group of nine phthalic acid esters and one adipate from three types of coffee (maximum intensity, intermediate intensity and decaffeinated) prepared from coffee capsules, using gas chromatography coupled to mass spectrometry for analytes separation and determination. Matrix-matched calibration showed good linearity with determination coefficients (R 2 ) higher than 0.9983 for all analytes and matrices. In general, matrix effect assessment revealed a medium effect of signal suppression, while mean relative recovery values were in the range 70–120% with relative standard deviation values ≤19% for most analytes. Several samples of each type of coffee obtained from capsules made of different materials were also analysed, finding concentrations of DBP, DEHA and DEHP in the range 29.3–734 ng/capsule, below the tolerable daily intake established for some of them.